A Truly Boundary-Only Meshfree Method Applied to Kirchhoff Plate Bending Problems (Advances in Applied Mathematics and Mechanics, 2018)
The boundary particle method (BPM) is a truly boundary-onlycollocation scheme, whose basis function is the high-ordernonsingular general solution or singular fundamental solution, basedon the recursive composite multiple reciprocity method (RC-MRM). TheRC-MRM employs the high-order composite differential operator tosolve a much wider variety of inhomogeneous problems withboundary-only collocation nodes while significantly reducingcomputational cost via a recursive algorithm. In this study, wesimulate the Kirchhoff plate bending problems by the BPM based onthe RC-MRM. Numerical results show that this approach producesaccurate solutions of plates subjected to various loadings withboundary-only discretization.